Suicide after Facebook posts-An unnoticed departure of life in Bangladesh - Md. Rabiul Islam; MMA Shalahuddin Qusar; Md. Saiful Islam (Elsevier, 2021)
Social networking sites have changed the concept of social interaction and communication. There is increasing evidence of using Facebook to express suicidal ideas and feelings, predominantly among young people. Here, we report a series of cases where victims committed suicide after sharing their thoughts and feelings on Facebook posts or live-streaming. In the present case series, we observed most of the victims were teenagers and young adults. Usually, this group is unwilling to share their suicidal thoughts with physicians or other family members. At the same time, they like to share those factors on Facebook or other social networking sites. So, Facebook can be a potential tool to predict and prevent such suicide cases. A better understanding and quick response to suicidal notes on Facebook can prevent many lives. The present study suggests ensuring the active participation of Facebook users in suicide prevention programs. We can work together with suicide prevention tools and strategies of social networking sites to save many unwanted departures.